The Use of Multiplication Wheel Media in Learning Mathematics to Improve Counting Abilities - Amiyati, Fanni Rara; Saputri, Fita; Destiana Sari; Finorina, Finorina (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to improve students' creativity in learning mathematics, especially in multiplication material, by utilizing innovative media called Kincir Pintar Perkalian. This media is designed to help students understand the concept of multiplication in a more fun and interactive way. This study uses the Classroom Action Research (CAR) method, which consists of two cycles. Each cycle includes planning, implementation, observation, and reflection stages. The study's first cycle results showed that the average student score reached 70, with a 60% success rate achieving the Minimum Completion Criteria (KKM). However, there was a significant increase after improvements and adjustments were made in the second cycle. The average student score increased to 82, with a 90% success rate achieving the KKM. This study's results prove that using multiplication wheel media improves students' understanding of multiplication. Interesting visualizations and interactive learning methods make students more motivated to learn. In addition, a creative and fun approach helps students understand multiplication better. With the increase in learning outcomes, this media improves students' numeracy skills and stimulates their creativity. Therefore, the Smart Multiplication Wheel is recommended as an innovative learning media in Elementary Schools to support the development of students' creativity and numeracy skills in mathematics.